Pengaruh Intensitas Penggunaan Platform Digital, Kepercayaan Terhadap Pemerintah, dan Persepsi Kemudahan Penggunaan Sistem Pajak Digital Terhadap Kesadaran Membayar Pajak pada Wajib Pajak Generasi Milenial di Era Transformasi Digital (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Digital transformation has driven the modernization of the tax system in Indonesia. This study aims to analyze the influence of the intensity of digital platform use, trust in the government, and perceived ease of use of the digital tax system on tax awareness among millennial taxpayers. The study used a quantitative approach with a causal associative method. Data were collected through questionnaires distributed to 62 millennial taxpayers selected using a purposive sampling technique. The data were then analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that the intensity of digital platform use and trust in the government had a positive and significant effect on tax awareness, while the perceived ease of use of the digital tax system had no significant effect. These findings indicate that optimizing the use of digital platforms and increasing public trust in the government are important factors in improving tax awareness among millennials